Intelligent Decision Support System for Production Planning and Control in an Automotive Assembly Line - Nitin Pal (International Journal of Industrial and Product Design Engineering, 2023)
The automobile industry has realized the importance of Intelligent Decision Support Systems (IDSS) to improve production planning and control on assembly lines. In the context of automobile manufacturing, this review paper examines the most recent developments, methodology, and applications of IDSS. Key trends, obstacles, and possibilities are discovered through an in-depth examination of the literature. Examining real-world case studies and success stories, the integration of artificial intelligence (AI) and machine learning (ML) approaches in IDSS is studied. In addition, the study discusses current difficulties and suggests solutions. This review intends to steer future research and development in IDSS for automotive assembly lines, emphasizing its potential to increase productivity and efficiency in the sector. It does this by outlining future directions and emerging trends.
Keywords: IDSS; Machine Learning; Optimization; artificial intelligence; quality control